Disseminated Herpes Zoster Subsequent to Ocular Shingles in an Immunocompetent Young Man Following Facial Trauma: A Case Report - Grady, Grady; Rahayu, Dewa Ayu Putu Mitha Paramitha; Saraswati, Putu Dyah Ayu (Riviera Publishing, 2025)
Herpes zoster (HZ) results from the reactivation of latent varicella-zoster virus (VZV), typically triggered by aging or immunosuppression. Herpes zoster ophthalmicus (HZO) affects the ophthalmic branch of the trigeminal nerve (V1), posing a risk of ocular complications. Disseminated herpes zoster (DHZ), a rare form of HZ, is defined by ?20 vesicular lesions beyond the primary and adjacent dermatomes, potentially leading to systemic complications and increased morbidity. Case Presentation: A 36-year-old immunocompetent male presented with disseminated vesicular eruptions across the body, sparing the knees and lower legs, four days after the initial appearance of vesicles along the left ophthalmic (V1) branch of the trigeminal nerve. Notably, the patient had a history of minor trauma at the same site one week prior. A comprehensive evaluation and multidisciplinary management were undertaken, involving ophthalmologists, dermatologists, and neurologists. By the third day of treatment, his pain had significantly subsided, no new lesions had developed, and was discharged. Conclusion: DHZ can occur in immunocompetent individuals at any age, but is more common in older patients. A meticulous history and physical examination are essential, as dermatomal herpes zoster may progress to dissemination. Additionally, the potential link between recent trauma and zoster reactivation may play a contributory role, highlighting the importance of early recognition for prompt intervention.